Passive Solar and Conventional Housing Design: A Comparative Study of Daylighting Energy Efficiency Potential - Overen, Ochuko K.; Meyer, Edson L.; Makaka, Golden (Frontiers in Energy Research, 2021)
The increasing energy consumption and its resultant CO2 emission in the built environment have revolutionised housing design. Buildings are strategically designed to harness ambient weather factors for indoor space thermal conditioning and lighting. A comparison of the daylighting and potential environmental mitigations due to the lighting energy consumption in a passive solar and the conventional house is the aim of this study. Both houses used as a case study are in Alice, Eastern Cape in South Africa. The indoor illuminance of the homes was monitored using Li-Cor 210R photometric sensors. Between 07h00 to 16h30, the passive solar house's average daylighting was 217 lux and 56 lux in the conventional house on a clear sky. Under the same sky condition, 47% lighting energy savings and mitigations of all environmental elements emitted and used by a coal-fired plant in generating the equivalent energy saved was obtained in the passive solar house. From the findings, daylight harvest through passive solar design shows the potential of energy savings and environmental mitigation measures in the housing sector.